Implementation of Principals' Leadership in Optimizing the Quality of Learning at Mis Yaa Bunayya Fathul Khair - Syadidah, Fathiyah; Tolla, Ismail; Faridah, Faridah (Indonesian Journal of Educational Studies, 2025)
Abstract: This study aims to describe the implementation of the principal's leadership in improving the quality of learning at MIS Yaa Bunayya Fathul Khair. The results show that school principals play a strategic role as decision makers, motivators, facilitators, and role models. The leadership style applied is a combination of transformational and democratic. Transformationally, school principals encourage technology-based learning innovations such as Virtual Reality (VR) and Jasoz HI-FI, as well as instill the value that teaching is worship. Democratically, school principals involve teachers in decision-making, open communication spaces, and support professional development through training. The impact can be seen in increasing teacher motivation and professionalism, strengthening religious culture, and learning effectiveness. Despite challenges such as differences in teacher backgrounds and student discipline, principals continue to encourage innovation and collaboration. This integrative and adaptive leadership has been proven to be able to optimize the quality of learning as a whole.